2013
DOI: 10.4321/s1886-36552013000400007
|View full text |Cite
|
Sign up to set email alerts
|

Herbal medicines supplied by community pharmacies in Lagos, Nigeria: pharmacists´ knowledge

Abstract: BackgroundThe use of herbal medicines is on the increase globally and they are usually supplied in pharmacies as non-prescription medicines. Pharmacists are, therefore, responsible for educating and informing the consumers about rational use of herbal medicines.ObjectiveTo evaluate the knowledge of pharmacists in Lagos, Nigeria with regards to the herbal medicines they supplied by their pharmacies.MethodsPharmacists in charge of randomly selected 140 community pharmacies from 20 Local Government Areas in Lagos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 36 publications
5
20
0
Order By: Relevance
“…Pharmacists may be considered as less knowledgeable on herbal drugs. A study done in Qatar and Nigeria reported poor knowledge of pharmacists with regard to herbal drugs [17, 18]. In the present study, females more frequently received questions related to drug dosage ( P = 0.032) and herbal drugs ( P = 0.016) compared to male pharmacists.…”
Section: Discussionsupporting
confidence: 39%
“…Pharmacists may be considered as less knowledgeable on herbal drugs. A study done in Qatar and Nigeria reported poor knowledge of pharmacists with regard to herbal drugs [17, 18]. In the present study, females more frequently received questions related to drug dosage ( P = 0.032) and herbal drugs ( P = 0.016) compared to male pharmacists.…”
Section: Discussionsupporting
confidence: 39%
“…Y.Y.Noha: The Prevalence, Attitude and Awareness of Herbal Medicine Products Use Among Pharmacy Practitioner in Jordan similar findings to our study regarding awareness of interactions and adverse effects that they were inadequate. 18 A cross-sectional study in Saudi Arabia was conducted in 2012 documented that 9.1% just interested in herbal medicines lack of time was the most common barriers that limit discussing herbal medicine products, lack of scientific evidence that supports herbal. medicine use and lack of reliable resources, or lack of knowledge of herbal medicines, so it is necessary to educate and training pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…The content of the questionnaire was generated by reviewing the literature [10,[13][14][15][16][17][18]. No guidance or assistance was provided to participants as they completed the questionnaire during their visit to the pharmacy.…”
Section: Questionnairementioning
confidence: 99%
“…Health care providers have a professional responsibility to advise patients about potentially harmful aspects of herbal remedies, including contraindications or interactions with synthetic medications [9]. Previous studies from Nigeria, Kuwait, the United Arab Emirates and Australia have shown that most community pharmacists do not possess enough knowledge about the potential interactions and side effects of herbal medicines that they supply [10][11][12].…”
Section: Introductionmentioning
confidence: 99%